Electrospinning of Fe-doped ZnO nanoparticles incorporated polyvinyl alcohol nanofibers for its antibacterial treatment and cytotoxic studies. (September 2019) - Sekar, Aiswarya Devi; Kumar, Vinay; Muthukumar, Harshiny; Gopinath, P.; Matheswaran, Manickam
Graphical abstract: Electrospinning of Fe-doped ZnO@PVA NFs with good antimicrobial and cytocompatibility. Highlights: Successful fabrication of PVA NFs with NPs for antibacterial application. SEM micrographs corroborated the morphology of NFs with diameters 120 to 250 nm. The antibacterial activity has increased with the increase in wt% of nanoparticles in NFs. The Fe-doped ZnO NPs@PVA NFs has delivered good cytocompatibility towards MCF-7 cells. Abstract: Poly Vinyl Alcohol (PVA) nanofibers incorporated with various weight percentages of Fe-doped ZnO nanoparticles were successfully fabricated by electrospinning technique and examined for its antibacterial with cytotoxic properties. The analytical characterization of fabricated nanofibers has revealed virtuous physicochemical traits such as bead less uniform nanofibers with diameter ranges from 120 to 250 nm and hydrophilic in nature. A prominent bactericidal activity of nanofibers was detected with the increase in Fe-doped ZnO nanoparticles (NPs) concentration against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli, bacterial strain. The maximum growth inhibition was found to be 88% and 66% for E. coli and S. aureus organism. The cytotoxic nature of the nanofibers was studied against MCF-7 cells using MTT. The viability of MCF 7 cell lines were reduced only meagerly with increase in concentration of nanoparticles in PVA nanofibers (NFs). Thus the Fe-doped ZnO incorporated PVA NFs could be one of the pioneering materials suitable for various biomedical applications.